Loss of Mitochondrial Genetic Diversity in Overexploited Mediterranean Swordfish (Xiphias gladius, 1759) Population - Tommaso Righi; Andrea Splendiani; Tatiana Fioravanti; Elia Casoni; Giorgia Gioacchini; Oliana Carnevali; Vincenzo Caputo Barucchi (Diversity, 2020)
Intense and prolonged mortality caused by over-exploitation could drive the decay of genetic diversity which may lead to decrease species’ resilience to environmental changes, thus increasing their extinction risk. Swordfish is a high commercial value species, especially in the Mediterranean Sea, where it is affected by high catch levels. Mediterranean swordfish consist of a population genetically and biologically distinct from Atlantic ones and therefore managed as a separate stock. The last Mediterranean swordfish stock assessment reported that in the last forty years Mediterranean swordfish has been overfished and, to date, it is still subject to overfishing. A comparison between an available mitochondrial sequence dataset and a homologous current sample was carried out to investigate temporal genetic variation in the Mediterranean swordfish population over near twenty years. Our study provides the first direct measure of reduced genetic diversity for Mediterranean swordfish during a short period, as measured both in the direct loss of mitochondrial haplotypes and reduction in haplotype diversity. A reduction of the relative females’ effective population size in the recent sample has been also detected. The possible relationship between fishery activities and the loss of genetic diversity in the Mediterranean swordfish population is discussed.